Service-Based Leadership in Islamic Schools - Putri Chusnul Khotimah; Budi Haryanto; Eni Fariyatul Fahyuni (Proceedings of The ICECRS, 2020)
This paper discusses service-based leadership in Islamic schools. Leadership demands a transformation from the heart and changes in character. True leadership starts from within and then moves outside to serve those they lead. This is where the importance of the character and integrity of a leader to become a true leader and accepted by other people or parties. This research is a qualitative-descriptive research which is expected to be able to uncover various information with a careful and meaningful description-analysis. Data sources in this study include principals, staff, students. Data collection is done by interview, observation, and documentation. As for the data analysis techniques through the stages of data reduction, data presentation and data analysis. The results of this research are (a) the principal's leadership has a variety of models that are extraordinary depending on the situation and conditions. (b) Service-based leadership is a new trend for achieving desired quality goals.